The effectiveness of al-qur'an healing with audio-visual methods in reducing pain in the active phase of the first stage of labor - Suri Salmiyati; Yulia Fauziah Amizuar (Universitas 'Aisyiyah Yogyakarta, 2020)
Pain that occurs during labor is caused by the activity of uterine contractions. Uncontrolled pain can cause stress that will inhibit the release of the hormone oxytocin so that the labor process is disrupted. Labor pain can be decreased by pharmacological methods (drugs) or non-pharmacological ones, such as Al-Qur'an Healing with audio-visual methods. This study aims to determine the effect of Al-Quran Healing with audio-visual methods on the level of pain in the active phase of the first stage of labor. This study was an experimental quantitative research with one group pretest-posttest research design. The sampling technique was accidental sampling technique with the total of 12 samples. The research instruments were the videos of Al-Qur'an Surah Al-Insan, Al-Mulk, Maryam and Al-Kahf. The pain assessment instrument used Numeric Rating Scales. The data analysis in this study used univariate and bivariate analysis. Based on the univariate test, it was found that the respondents’ characteristics were ages that were not at risk and multiparous parity. Most respondents were high-school graduates and were assisted by their husbands during the labor. The results of data analysis using Wilcoxon obtained p-value 0,035 (p α) meaning that there was difference in the level of labor pain before and after the intervention. It could be concluded that there was a significant effect of giving Al-Qur'an Healing therapy to the level of labor pain in the active phase of the first stage of labor. This method of therapy is recommended to be used by the mothers during labor, and it is expected that the health services and the health workers can facilitate it.